2013
DOI: 10.1111/ijcp.12187
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in imaging and associated radiation exposure in inflammatory bowel disease

Abstract: Approximately 1 in 13 patients in the study cohort were exposed to potentially harmful levels of ionising radiation. Strategies to minimise exposure to diagnostic medical radiation in IBD patients are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
3
18
1
Order By: Relevance
“…Between 2002 and 2007, there was a reported 840% increase in the use of CT enterography in IBD patients in Minnesota, United States [6] . Similarly, a 310% increase in use of abdominal CT imaging was reported in a United Kingdom study of IBD patients between 1990 and 2010 [14] . CT imaging offers the advantages of widespread availability, rapid acquisition of images, high sensitivity and specificity for the detection of intramural and extra-intestinal disease, as well as being well tolerated by patients [4] .…”
Section: Ulcerative Colitismentioning
confidence: 69%
See 2 more Smart Citations
“…Between 2002 and 2007, there was a reported 840% increase in the use of CT enterography in IBD patients in Minnesota, United States [6] . Similarly, a 310% increase in use of abdominal CT imaging was reported in a United Kingdom study of IBD patients between 1990 and 2010 [14] . CT imaging offers the advantages of widespread availability, rapid acquisition of images, high sensitivity and specificity for the detection of intramural and extra-intestinal disease, as well as being well tolerated by patients [4] .…”
Section: Ulcerative Colitismentioning
confidence: 69%
“…A recent United Kingdom retrospective study of 415 patients with IBD referred from primary care, reported a median total CED of 7.2 mSv in CD patients and 2.8 mSv in UC patients, with 8% of IBD patients overall exposed to CED > 50 mSv. Kaplan Meier analysis projected a probability of exposure to CED > 50 mSv of 6% and 14% at 10 years and 15 years from IBD diagnosis respectively (figure 1) [14] . Concerningly, a retrospective study of IBD patients in South Korea, conducted across 13 university hospitals, reported even higher proportions of patients exposed to potentially harmful radiation levels.…”
Section: Ibd Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Multiple studies have reported elevated levels of radiation exposure among patients with inflammatory bowel disease, including subsets of up to 21% with cumulative-effective doses in excess of 75 mSv. [26][27][28][29][30][31][32][33][34] A recent study following 451 patients over 11 years found that by a median age of 40 years, 16% were exposed to a high radiation levels (a cumulative effective dose >50 mSv) and that 4% had a cumulative effective dose greater than 100 mSv. 35 Although controversial, the widely used linear-no-threshold unadjusted risk model adopted by the Biologic Effects of Ionizing Radiation VII Conference holds that a 10-mSv exposure increases one's lifetime attributable risk of cancer by 1/1,000 above baseline.…”
Section: Imaging and Associated Radiation Exposure Among Patients Witmentioning
confidence: 99%
“…A retrospective cohort study of 415 patients over 20 years found that usage of CTs increased by 310 % and that 1 in 13 patients was exposed to potentially harmful levels of ionizing radiation defined as CED [50 mSv. A history of IBD-related surgery was a risk factor for high exposure [10]. CD patients are commonly diagnosed in their 20s and 30s with *20 % diagnosed during childhood [11].…”
mentioning
confidence: 99%